Sex determination & morphometric parameters of human mandible - Kumar, M. Punarjeevan; Lokanadham, S. (International Journal of Research in Medical Sciences, 2017)
Goal: The knowledge about the anatomy of the mandible and its variations in age, sex and race will help physicians, surgeons, medico-legal authorities and anthropologists to give correct interpretations for the diagnostic procedures in living. Methods: We collected the human mandible bones (N=80) from the department of Anatomy, SVIMS university and around the Tirupati region to study the morphological and morphometric features by using 22 different parameters. Results: Among 22 parameters Six dominating parameters that possibly explain the nature of the mandible are height of the ramus, body thickness, anthropometric arch width, inter incisor width, mandibular index and mandibular angle are useful to determine the unknown sex of the mandible upto an extent of 75.2% in south Indian population. The incidence of the above mentioned sex determination parameters considered together and treated statistically. Conclusion: The present study reveals that the mandible of unknown gender can be sexed to the extent of 75% accuracy by six dominating parameters and not to consider these for complete sex determination of the mandible bone in osteometric studies.